Alternative Therapies to Bacillus Calmette-Guérin Shortage for Nonmuscle Invasive Bladder Cancer in Brazil and Other Underdeveloped Countries: Management Considerations - Wroclawski, Marcelo Langer (J Glob Oncol, 2019)
Bacillus Calmette-Guérin (BCG) plays a cornerstone role in the management of nonmuscle invasive urothelial carcinoma of the bladder. However, there has been a worldwide intermittent BCG shortage in recent years that may affect the care of patients with bladder cancer and pose difficult clinical decisions to urologists and clinical oncologists. This literature review aims to clarify alternatives to BCG during a shortage and propose measures to replace BCG, mainly in Brazil and probably in other low- and middle-income countries, where not all studied and commonly suggested treatments are available.